The Influence of Islamic Teachings on Students' Attitudes towards Social Justice - Siti Aminah; Siti Mahmudah; Siti Sumadiyah (ISEDU : Islamic Education Journal, 2026)
The purpose of this study is to examine the influence of Islamic teachings on students' attitudes towards social justice, with a particular focus on how values such as equality, compassion, fairness, and community responsibility are internalized in educational settings. Using a qualitative approach supported by descriptive analysis, the research explores how students perceive and practice social justice principles in their daily interactions, academic environment, and community engagement. The findings reveal that Islamic teachings, when integrated into both formal and non-formal education, significantly shape students’ perspectives on justice and fairness, fostering empathy, tolerance, and a sense of responsibility toward marginalized groups. Furthermore, the study highlights the role of teachers, religious education, and institutional culture in reinforcing these values. This research contributes to a deeper understanding of the transformative role of religion in promoting social justice among the younger generation, particularly within Islamic education contexts.